2022
DOI: 10.3390/antiox11091705
|View full text |Cite
|
Sign up to set email alerts
|

Icariside II Exerts Anti-Type 2 Diabetic Effect by Targeting PPARα/γ: Involvement of ROS/NF-κB/IRS1 Signaling Pathway

Abstract: Type 2 diabetes mellitus (T2DM) is a multisystem and complex metabolic disorder which is associated with insulin resistance and impairments of pancreatic β-cells. Previous studies have shown that icariside II (ICS II), one of the main active ingredients of Herba Epimedii, exerts potent anti-inflammatory and anti-oxidative properties. In this study, we investigated whether ICS II exerted anti-T2DM profile and further explored its possible underlying mechanism both in vivo and in vitro. db/db mice were administe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…19 For example, icariside II (ICA-II), a natural prenyl-flavonol and the active component of Epimedium koreanum (E. koreanum), has been shown to have anti-inflammatory 20 and anti-cancer 21 activities, has protective effects in rodent models of Alzheimer's disease, 22 and mediates anti-hepatotoxic, 23 anti-tumor, 24 antiosteoporosis, and osteonecrosis effects. 25 It protects against acute ischemic stroke 26 and diabetes, 27,28 improves myocardial fibrosis, 29 and attenuates streptozotocin-induced cognitive deficits. 30 We have previously reported that the flavonoid gossypetin has analgesic effects in mouse models of inflammatory and neuropathic pain.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 For example, icariside II (ICA-II), a natural prenyl-flavonol and the active component of Epimedium koreanum (E. koreanum), has been shown to have anti-inflammatory 20 and anti-cancer 21 activities, has protective effects in rodent models of Alzheimer's disease, 22 and mediates anti-hepatotoxic, 23 anti-tumor, 24 antiosteoporosis, and osteonecrosis effects. 25 It protects against acute ischemic stroke 26 and diabetes, 27,28 improves myocardial fibrosis, 29 and attenuates streptozotocin-induced cognitive deficits. 30 We have previously reported that the flavonoid gossypetin has analgesic effects in mouse models of inflammatory and neuropathic pain.…”
Section: ■ Introductionmentioning
confidence: 99%
“…koreanum), has been shown to have anti-inflammatory and anti-cancer activities, has protective effects in rodent models of Alzheimer’s disease, and mediates anti-hepatotoxic, anti-tumor, anti-osteoporosis, and osteonecrosis effects . It protects against acute ischemic stroke and diabetes, , improves myocardial fibrosis, and attenuates streptozotocin-induced cognitive deficits …”
Section: Introductionmentioning
confidence: 99%